Strang-Fix theory for approximation order in weighted Lp-spaces and Herz spaces - Naohito Tomita (Journal of Function Spaces and Applications)
In this paper, we study the Strang-Fix theory for approximation order in the weighted Lp -spaces and Herz spaces.